1998
DOI: 10.1021/jf9802934
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Panel of Immunoassays for Monitoring DDT, Its Metabolites, and Analogues in Food and Environmental Matrices

Abstract: A panel of antisera was prepared using analogues and derivatives of metabolites of the organochlorine insecticide, p,p′-DDT as haptens. The assays developed exhibited differing cross-reactions for different DDT analogues and metabolites, and the choice of hapten for the detecting enzyme conjugate had almost as much effect on assay specificity and sensitivity as the structure of the hapten used for antibody production. Those assays developed using hapten I, based on esters of bis(pchlorophenyl)acetic acid (DDA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…Limits of detection were approximately one order of magnitude lower than colorimetric ELISAs (Abad et al, 1997;Hochel and Musil, 2002) and slightly better than chemiluminescent ELISAs (Botchkareva et al, 2003). Among immunoassay methods used for DDT detection (Beasley et al, 1998;Valentini et al, 2003), only one work (Anfossi et al, 2004), based on a non-competitive immunoassay format, has reported slightly lower detection limits (8 ng L −1 ) than our SPR immunoassay format.…”
Section: Sensitivity Of Ddt Analysismentioning
confidence: 68%
“…Limits of detection were approximately one order of magnitude lower than colorimetric ELISAs (Abad et al, 1997;Hochel and Musil, 2002) and slightly better than chemiluminescent ELISAs (Botchkareva et al, 2003). Among immunoassay methods used for DDT detection (Beasley et al, 1998;Valentini et al, 2003), only one work (Anfossi et al, 2004), based on a non-competitive immunoassay format, has reported slightly lower detection limits (8 ng L −1 ) than our SPR immunoassay format.…”
Section: Sensitivity Of Ddt Analysismentioning
confidence: 68%
“…Chickens were immunized with DDA-hapten to generate antibodies against DDT. The synthesis of DDA-hapten has been described by (Beasley et al, 1998). DDT and DDA found to show more than 95% cross reactivity.…”
Section: Preparation Of Immunoassay Reagentsmentioning
confidence: 99%
“…In addition, the characterization of the polyclonal antibody indicated that the antiserum possesses a high specificity for p,p -isomers. Botchkareva et al [13] have developed the most sensitive ELISA with chemiluminescent detection for DDT compounds compared to the methods found in the literature; [11,12,15,16] for the DDT-selective assay, a limit of detection was estimated at 0.06 ng/mL. On the other hand, the detection limit of p,p -DDT in the EIA system developed in this study was about two times lower sensitivity than that in the DDT-selective assay reported by Botchkareva et al [13] However, in this study, the EIA system using antip,p -DDT antibody showed very high specificity for the parent compound p,p -DDT when compared with most previously published assays.…”
Section: Resultsmentioning
confidence: 99%